A patient-derived tumoroid platform for NF1 low-grade glioma shows myeloid evolution and shifting metabolic dependencies during in vitro culturing - David R. Beale; Isabella A. DiStefano; Stephanie Brosius; Jonathan H. Sussman; Isabella Seka; Ryan Lingerak; Angela Viaene; Mariarita Santi; Peter J Madsen; Phillip B Storm; Adam Resnick; Kai Tan; et al. (Acta Neuropathologica Communications, 2026)
Abstract About 10–15% of individuals with Neurofibromatosis Type 1 develop a low-grade glioma (LGG) within the optic pathway, and an additional 3–5% of individuals develop LGG outside of the optic pathway. In recent years molecular analysis has greatly enhanced our understanding of what drives these NF1 LGG; however, to date in vitro and in vivo models are rare. Here, we present the first in vitro tumor-derived spheroid cultures (tumoroids) of 3 NF1-associated LGGs grown for up to 4 weeks that can be passaged and banked. To determine how accurately the NF1 LGG tumoroid cultures reflect human disease, and how much and how quickly they drift from the primary tumors, we performed single nuclear RNAseq (snRNA-seq) analysis on primary tumor and 1, 2 and 4 weeks in culture for one of these NF1 LGG tumoroid lines. Observations were confirmed with immunofluorescence staining on all 3 lines. As expected, the few CD3 + T-cells present in the primary tumor are lost by day 14 (IF) and not detected on scRNAseq; macrophages/microglia remain present for at least 14 days but are largely depleted by week 4. Additionally, we observe a shift from more homeostatic microglia in the primary tumor to CD163 positive tumor-associated macrophages/microglia (TAM) in vitro. Neoplastic clusters uniquely associated with the primary tumor had clear upregulation of genes associated with neuronal communication. Our analysis also shows that primary NF1 LGGs rely on the metabolism of fatty acids (FA) for energy, while in vitro, the primary energy source shifts to glucose. Additionally, instead of metabolizing FA, both neoplastic and immune cells switch to FA synthesis in vitro. Finally, we observe a slightly increased proliferative index in vitro versus in vivo, both in neoplastic and immune cells. We conclude that these NF1 LGG tumoroid cultures have the highest fidelity in the first few weeks of culture, giving us a time window to study primary NF1 LGG biology or to assess therapeutic vulnerabilities. Finally, optimizing media conditions, for example to reduce glycolysis and support FA synthesis, could extend the period of highest fidelity for NF1 LGG tumoroids.